Villages e-government - Setiawan A.I.; Nguyen P.T.; Perumal E.; Shankar K.; Abadi S.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
A computer technology plays a very important role for development in all fields. The rapid development of information technology greatly affects the agency's performance, because the time could be utilized more effectively and efficiently. Pekon, is a Lampung's word, means village. The existence of an information system in Pekon Way Jaha is very helpful for the community and the government to run data browser. and it is useful to provide an overview of what is presented in Pekon Way Jaha. By the existence of this system, the data can be searched faster so that it can minimize time, costs and errors that may occur. The existence of a computerized system in a field, can facilitate the data recording and processing, reduce errors in recording, and produce reports based on certain categories as needed. BEIESP.